1996
DOI: 10.1001/archsurg.1996.01430190097023
|View full text |Cite
|
Sign up to set email alerts
|

Moderation of Anal Sphincter Tone With Nitric Oxide Agonists and Antagonists

Abstract: These data indicate that the action of agonists and antagonists of nitric oxide synthesis carries across the anorectal mucosa and rapidly modifies sphincter tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…[23][24][25] In-vivo studies 26,27 using low-compliance, continuously perfused catheters to measure resting anal pressures in opossums have demonstrated that nitric oxide synthase inhibitor reverses the decrease in baseline pressure in response to either rectal distention or sacral nerve stimulation. The only in-vivo study 9 investigating the effect of exogenous L-arginine on the internal anal sphincter showed that L-arginine (in concentrations ranging from 0.01 mg to 10 mg), when introduced into the rectum of gently restrained unanesthetized rats, caused a significant reduction in sphincter pressures (P Ͻ 0.05), with higher concentrations of arginine causing a more rapid fall in ARP and the maximal effect being reached at 30 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] In-vivo studies 26,27 using low-compliance, continuously perfused catheters to measure resting anal pressures in opossums have demonstrated that nitric oxide synthase inhibitor reverses the decrease in baseline pressure in response to either rectal distention or sacral nerve stimulation. The only in-vivo study 9 investigating the effect of exogenous L-arginine on the internal anal sphincter showed that L-arginine (in concentrations ranging from 0.01 mg to 10 mg), when introduced into the rectum of gently restrained unanesthetized rats, caused a significant reduction in sphincter pressures (P Ͻ 0.05), with higher concentrations of arginine causing a more rapid fall in ARP and the maximal effect being reached at 30 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…9 The present study evaluates the effect of a single dose of topical L-arginine (the substrate for nitric oxide synthase) on maximum anal resting pressure (MARP) in volunteers and the incidence of side effects after repeated dosing to assess whether it may have potential as a new treatment for anal fissure.…”
mentioning
confidence: 99%
“…18 The method proved to be satisfactory for measuring the sphincter pressure in rats, with the findings comparable to those of the literature. 19,20 The measures of sphincter pressure performed before diabetes induction did not show a statistically significant difference …”
Section: Discussionmentioning
confidence: 90%
“…This evidence for a nitric oxide-independent mechanism underlying the effect on isolated anal sphincter stands in marked contrast to observations in the rat. Topical application of L-arginine to the anal and rectal mucosa in male Sprague-Dawley rats significantly reduced anal sphincter pressure and this effect was reversed by subsequent application of L-NAME 19 . The difference between the in vitro observation in sheep IAS and the in vivo observations in the rat raises the possibility that Larginine may increase nitric oxide formation in a cell type not found in vitro (non-smooth muscle, non-neuronal).…”
Section: Discussionmentioning
confidence: 93%